Web-Based School Academic Information System: Case Study at an MTs School in Bandung - Wahyudin Wahyudin; Heri Wahyudi; Komarudin Komarudin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Academic management activities are an essential part of the world of education related to the teaching and learning process. Currently, the academic information system at one MTs school in Bandung is still being done manually, such as recording student data, teacher data, subject data, scheduling data, and class data. However, this method is considered less effective because it is prone to damage or loss of data. This study aims to develop a system for data collection in teaching and learning activities. In developing the academic system, the author uses a qualitative descriptive method, in which data collection is carried out through triangulation, data analysis is inductive/qualitative, and research results emphasize meaning rather than generalization, emphasizing use cases. The programming language used to design and implement this academic information system is PHP with SSL, and the database used is MySQL. The results of this research can assist Curriculum officers and teachers in managing student data, teacher data, subject data, scheduling data, and class data more quickly and reduce the risk of data damage or loss.